Genotyping of soybean cultivars of Kazakhstan with the use of ISSR-markers (Experimental biology, 2019)
ISSR-analysis of soybean cultivars was done. Phylogenetic relationships among Kazakhstan’s cultivars were studied. The level of genetic diversity of soybean of Kazakhstan was evaluated.